Comparison of Clinical Efficacy of Liquid-Based Cytology and High-Risk Human Papillomavirus Testing With Partial Genotyping in Cervical Screening of Women Below 30 Years Old - Joella Xiaohong Ang MMed; Sun Kuie Tay FRCOG (Cancer Control)
Introduction We evaluated the clinical efficacy of primary Human Papillomavirus (HPV) testing and liquid-based cytology (LBC) for cervical screening in women below 30 years old. Methods This was a retrospective analysis of data collected prospectively from women 25 years or older who attended hospital-based gynaecology clinics for cervical screening. Simultaneous high-risk HPV testing with partial genotyping and LBC testing was performed. Comparison of clinical efficacy of HPV testing and LBC was performed for routine screening discharge rate, colposcopy referral rate, and number of colposcopies needed for each CIN2+ detected. Results Of 6398 women included, 503 women (7.9%) tested positive for HPV DNA. The positivity was higher for 25-to-29 years old than for women ≥30 years old (12.6% vs 7.3%, P < .001). The rate was markedly skewed by a low rate for women ≥45 years old. Similarly, more women below 30 years old (10.6%) had abnormal LBC results compared to women ≥30 years old (6.0%). Comparing LBC and HPV testing, the observed difference was not significant for discharge rate to interval screening (89.5% vs 87.4%). A higher referral to coloscopy rate (6.6 % vs 7.8%) was observed for HPV screening but the number of colposcopies for each detected CIN2+ (5 vs 7) was not significantly different. Clinical efficacy of HPV and LBC testing was similar in comparisons of women in 5-year groupings between 25 and 44 years old. Conclusions Our data indicated that cervical screening for women between 25 and 29 years old could adopt HPV screening as the older women.